Assessing thickness and stiffness of superficial/deep masticatory muscles in orofacial pain: an ultrasound and shear wave elastography study - Yunn-Jy Chen; Hui-Yi Lin; Cheng-An Chu; Wei-Ting Wu; Lan-Rong Chen; Levent Özçakar; Ke-Vin Chang (Annals of Medicine, 2023)
AbstractIntroduction Sonoelastography has been increasingly used for non-invasive evaluation of the mechanical features of human tissues. The interplay between orofacial pain and regional muscle activity appears clinically paramount, although only few imaging studies have investigated this association. Using shear wave sonoelastography (SWS), this study ascertained whether orofacial pain induced alterations in the stiffness of superficial and deep masticatory muscles.Methods All participants were systematically evaluated for oral/facial-related conditions, including the area and intensity of pain. SWS was applied to measure the stiffness of the bilateral masseter, temporalis, and lateral pterygoid muscles. The association between orofacial pain and muscle stiffness/thickness was investigated using a generalized estimating equation for adjusting the influence of age, sex, laterality, and body mass index on muscle thickness/stiffness.Results A total of 98 participants were included in the present study: 48 asymptomatic controls, 13 patients with unilateral pain, and 37 patients with bilateral orofacial pain. The reliability, quantified by the intraclass correlation coefficient for muscle stiffness measurement, ranged from 0.745 to 0.893. Orofacial pain at the individual muscle level was significantly associated with masseter muscle stiffness. A trend of increased stiffness (p = 0.06) was also observed in relation to the painful side of the temporalis muscle. No significant correlation was identified between the numeric rating scales for pain and stiffness measurements.Conclusions SWS provides reliable stiffness measurements for the superficial and deep masticatory muscles. The ipsilateral masseter and temporalis muscles might be stiffer than those on the side without orofacial pain. Future studies using the present sonoelasotography protocol can be designed to investigate the stiffness changes in the target muscles after interventions.